2020
DOI: 10.1017/s0033291720001555
|View full text |Cite|
|
Sign up to set email alerts
|

Psychological distress among health professional students during the COVID-19 outbreak

Abstract: Background. Due to the drastic surge of COVID-19 patients, many countries are considering or already graduating health professional students early to aid professional resources. We aimed to assess outbreak-related psychological distress and symptoms of acute stress reaction (ASR) in health professional students and to characterize individuals with potential need for interventions. Methods. We conducted a prospective cohort study of 1442 health professional students at Sichuan University, China. At baseline (Oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
208
4
12

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(242 citation statements)
references
References 7 publications
18
208
4
12
Order By: Relevance
“…Our findings regarding women's mental health burden align with other COVID-19 studies that have found higher rates of anxiety, depression, and stress using similar well-validated, self-report measures [4,10,12].…”
Section: Psychological Functioning During Lockdownsupporting
confidence: 88%
See 2 more Smart Citations
“…Our findings regarding women's mental health burden align with other COVID-19 studies that have found higher rates of anxiety, depression, and stress using similar well-validated, self-report measures [4,10,12].…”
Section: Psychological Functioning During Lockdownsupporting
confidence: 88%
“…This aligns with prior research identifying relationships between having a relative infected by COVID-19 [6,46], residing in a severely affected area [27,46,47], perceiving more daily impacts [5,11], and worse psychological functioning. Similarly, our finding that positive changes in response to COVID-19 were associated with lower levels of anxiety, stress, and depression converges with COVID-19-specific research on potential sources of resilience including good family functioning [10] and positive reappraisal [48].…”
Section: Psychological Functioning During Lockdownsupporting
confidence: 79%
See 1 more Smart Citation
“…Overall, COVID-19 studies in students are in line with our findings. Further studies on mental health in similar age groups that did not assess anxiety levels, point to the same direction of a negative impact of COVID-19 on other mental health outcomes [ 23 , 37 ]. The body of evidence, albeit still small, indicates the need to enhance mental health services in universities when such acute stressors occur.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, dealing with psychological impact of this pandemic on students' mental wellbeing is another issue that should not be overlooked. Isolated in quarantine, students are with no doubt suffering from anxiety at different levels [1,12,13]. The fear of the unknown, the social distancing and the direct impact of COVID 19 on their future practice.…”
Section: Introductionmentioning
confidence: 99%